Cost-effectiveness of postmastectomy hypofractionated radiation therapy vs conventional fractionated radiation therapy for high-risk breast cancer. (August 2021) - Yang, Jing; Qi, Shu-Nan; Fang, Hui; Song, Yong-Wen; Jin, Jing; Liu, Yue-Ping; Wang, Wei-Hu; Yang, Yong; Tang, Yu; Ren, Hua; Chen, Bo; Lu, Ning-Ning; et al.
Abstract: Background: The phase 3 NCT00793962 trial demonstrated that postmastectomy hypofractionated radiation therapy (HFRT) was noninferior to conventional fractionated radiation therapy (CFRT) in patients with high-risk breast cancer. This study assessed the cost-effectiveness of postmastectomy HFRT vs CFRT based on the NCT00793962 trial. Methods: A Markov model was adopted to synthesize the medical costs and health benefits of patients with high-risk breast cancer based on data from the NCT00793962 trial. Main outcomes were discounted lifetime costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER). We employed a time-dependent horizon from Chinese, French and USA payer perspectives. Model robustness was evaluated with one-way and probabilistic sensitivity analyses. Results: Patients receiving CFRT versus HFRT gained an incremental 0.0163 QALYs, 0.0118 QALYs and 0.0028 QALYs; meanwhile an incremental cost of 2351.92, 4978.34 and 8812.70 from Chinese, French and USA payer perspectives, respectively. Thus CFRT versus HFRT yielded an ICER of 144, 281.47, 420, 636.10 and 3, 187, 955.76 per QALY from Chinese, French and USA payer perspectives, respectively. HFRT could maintain a trend of >50% probabilities of cost-effectiveness below a willingness-to-pay (WTP) of 178, 882.00 in China, while HFRT was dominant relative to CFRT, regardless of the WTP values in France and the USA. Sensitivity analyses indicated that the ICERs were most sensitive to the parameters of overall survival after radiotherapy. Conclusions: Postmastectomy HFRT could be used as a cost-effective substitute for CFRT in patients with high-risk breast cancer and should be considered in appropriately selected patients. Highlights: HFRT is a cost-effective substitute for CFRT for women with high-risk breast cancer. The incremental cost-effectiveness ratio varied in a time-dependent manner and increased with the time horizon. Overall survival were the most influential parameter on the incremental cost-effectiveness ratio.